La aplicación del código de la niñez y adolescencia en el cumplimiento de derechos y deberes de los estudiantes del 5º año de educación general básica de la escuela fiscal mixta Isidro Ayora de la parroquia de Uyumbicho, cantón Mejía - Nato Chicaiza, Lourdes Raquel (2015)
The rights of children and teens are an important rule of law in the country because protects, the most vulnerable part of the population dependent on the physical and mental development, for this reason international legal instruments have been created that recognize these rights, the most important to this date is the Convention of the Rights of the Child Adopted by the United Nations, and it is in effect the Code on children and teens which collects a series of Rights among those Rights we have: Educational, healthy, dignity, healthy recreation, Rights to adequate food, a home, a family, not labor or sexual exploitation, to be Judged appropriately and corrected. The primary right is to education because it allows the student to live experiences in pursuit and expression of human existential sense. Parents are responsible for educating them, guide them and teach them to their children, trying to that demonstrate their education in any place that one finds.